Taxonomy of the genus Dactylanthias Bleeker (Teleostei: Serranidae: Anthiadinae) - Pogonoski, John J.; Gill, Anthony C. (Zootaxa, 2021)
The anthiadine genus Dactylanthias is reviewed. Two species, Dactylanthias aplodactylus (Bleeker, 1858) and Dactylanthias baccheti Randall, 2007 are currently recognised, each known only from their holotypes. A specimen of Dactylanthias matching D. baccheti in coloration was recently collected from Nauru in the West Pacific Ocean. It was retained by a recreational fisher and deposited into the CSIRO Australian National Fish Collection, Hobart. Data collected from this specimen and comparison to images of and data from the holotypes of both nominal species indicate that Dactylanthias baccheti Randall, 2007 is a junior synonym of Dactylanthias aplodactylus (Bleeker, 1858). Additional records of specimens from Ambon, Indonesia (type locality of D. apolodactylus) and the Maldives Islands, Indian Ocean are reported. The genus is briefly compared with other anthiadine genera.